METHODOLOGICAL PRINCIPLES OF CONDUCT OF EDUCATIONAL CLASSES WITH CADETS OF HIGHER ARMY EDUCATIONAL INSTITUTIONS AND MILITARY EDUCATIONAL UNITS OF INSTITUTIONS OF HIGHER EDUCATION TAKING INTO ACCOUNT THE EXPERIENCE OF THE LEADING COUNTRIES OF THE WORLD - Kucheriavyi, Andrii; Vanovska, Inna; Pyrogov, Kyrylo (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
B a c k g r o u n d . Modern approaches to the training of officers in Ukrainian institutions of higher military education, in particular with regard to the choice of methods of conducting classes, which have not yet gotten rid of the traditional Soviet military school, which ensured the formation of the performer’s personality. At the same time, the Russian-Ukrainian war demonstrates the demand for officers-leaders who are able to take the initiative and be independent in the decisions made and implemented, which causes a discrepancy between the results of the training of military personnel in domestic institutions of higher military education and the objective needs of the Armed Forces of Ukraine in officers of a certain quality, which determines the research problem. The following goal of the article was set: development of methodological principles for conducting training classes in higher military educational institutions of the leading countries of the world as such, which ensure the formation of the personality of a modern officer of the armed forces and require implementation in the educational process of domestic higher military educational institutions. A possible way to solve it will be the study and implementation in the domestic higher military school of the appropriate foreign experience of training officers, where the formation of a military leader is a long-standing tradition. M e t h o d s . Research methods – survey method, content analysis, experimental method, qualitative and qualitative research methods, sociological observation, system analysis, system approach, method of expert evaluations. R e s u l t s . Studying the experience of conducting classes in the USA and other leading countries of the world allows us to single out the methodological principles of training future officers, which was done by studying sources and by interviewing military personnel who studied at higher military educational institutions of NATO member countries. The conducted activities made it possible to establish that the methodological principles of training include the systematic use of active learning methods, prior independent work of cadets, ensuring the personal contribution of each of them to the study of topics, their active behavior in the lesson. C o n c l u s i o n s . The determined methodical principles made it possible to outline the ways and contribute to the difficulty of their implementation in the educational activity of domestic higher military educational institutions.